Perancangan Website Sistem Pengelolaan Surat Perusahaan Dengan Metode Waterfall Pada PT. Indo Mutiara Global - Ryanda Deanova; Fatmah, Adinda; Shafa Apta Hermawan, Lu’ay; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
Efficient management of company correspondence is a crucial component in supporting smooth operations and decision-making processes. PT. Indo Mutiara Global faces challenges in managing correspondence, which is still carried out manually using Ms. Excel, resulting in delays, recording errors, and difficulties in document retrieval. This research aims to design a correspondence management system based on the Waterfall method, enabling a systematic and structured development process. The design stages include requirements analysis, system design, implementation, testing, and maintenance. With this approach, the system is designed to meet the company's specific needs and ensure the system's quality and reliability before implementation. The research results show that the implementation of a correspondence management system based on the Waterfall model can improve recording accuracy, accelerate document retrieval processes, and reduce the risk of errors, thereby positively impacting the company's productivity and efficiency.